2008
DOI: 10.2174/1874189400802010032
|View full text |Cite
|
Sign up to set email alerts
|

What Factors are Associated with Where Women Undergo Clinical Breast Examination? Results from the 2005 National Health Interview Survey

Abstract: Background-Recent studies have suggested that clinical breast examination (CBE) rates may vary according to patient, provider and health care system characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…An additional finding was that uninsured patients (and those with Medicaid) had a more advanced stage of disease at diagnosis, as compared with patients with private insurance or Medicare (data not shown); it is in accord with what other research has indicated . The correlation between diagnoses of advance‐stage breast cancer among patients who are uninsured or have Medicaid insurance can be explained, in part, by reduced access to and/or utilization of cancer screening .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…An additional finding was that uninsured patients (and those with Medicaid) had a more advanced stage of disease at diagnosis, as compared with patients with private insurance or Medicare (data not shown); it is in accord with what other research has indicated . The correlation between diagnoses of advance‐stage breast cancer among patients who are uninsured or have Medicaid insurance can be explained, in part, by reduced access to and/or utilization of cancer screening .…”
Section: Discussionsupporting
confidence: 80%
“…Screening could affect the stage at diagnosis and screening rate is affected by insurance status . Insured women (68%) are more likely than uninsured women (35%) to have had a clinical breast examination .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of local communities (e.g., population SES, racial/ethnic composition) often influence the types of organizations that locate in particular settings, which may lead to differential access/availability of care to certain sub-populations [29, 30]. For example, racial/ethnic groups may prefer hospitals that recognize and address language or literacy barriers by employing translators; facilities that can afford to provide such services likely have different organizational characteristics from those facilities that do not.…”
Section: Methodsmentioning
confidence: 99%
“…Liyanage (2002) too reported a low coverage for cervical cancer screening in 2002 in the Kalutara district. These figures are quite low compared to 65% of CBE coverage within previous two years found among women over 40 years who had participated National Health Interview Survey in the United States of America in 2005 (Coughlin, 2008). Of the abnormalities detected by PHM, only the cases confirmed by the MOH are referred for specialist care and thus referral rate was only 86.8% instead of 100%.…”
Section: Discussionmentioning
confidence: 80%